Receptor usage and cell entry of bat coronavirus HKU4 provide insight into bat-to-human transmission of MERS coronavirus - Yang Yang; Lanying Du; Chang Liu; Lin‐Fa Wang; Cuiqing Ma; Jian Tang; Ralph S. Baric; Shibo Jiang; Fang Li (2014)
Middle East respiratory syndrome coronavirus (MERS-CoV) currently spreads in humans and causes ∼ 36% fatality in infected patients. Believed to have originated from bats, MERS-CoV is genetically related to bat coronaviruses HKU4 and HKU5. To understand how bat coronaviruses transmit to humans, we investigated the receptor usage and cell entry activity of the virus-surface spike proteins of HKU4 and HKU5. We found that dipeptidyl peptidase 4 (DPP4), the receptor for MERS-CoV, is also the receptor for HKU4, but not HKU5. Despite sharing a common receptor, MERS-CoV and HKU4 spikes demonstrated functional differences. First, whereas MERS-CoV prefers human DPP4 over bat DPP4 as its receptor, HKU4 shows the opposite trend. Second, in the absence of exogenous proteases, both MERS-CoV and HKU4 spikes mediate pseudovirus entry into bat cells, whereas only MERS-CoV spike, but not HKU4 spike, mediates pseudovirus entry into human cells. Thus, MERS-CoV, but not HKU4, has adapted to use human DPP4 and human cellular proteases for efficient human cell entry, contributing to the enhanced pathogenesis of MERS-CoV in humans. These results establish DPP4 as a functional receptor for HKU4 and host cellular proteases as a host range determinant for HKU4. They also suggest that DPP4-recognizing bat coronaviruses threaten human health because of their spikes' capability to adapt to human cells for cross-species transmissions.